Generation X and Generation Y restaurant employee perceptions of manager/employee relationships: a quantitative approach to understanding the arbitrating effects on turnover intent and manager relationship satisfaction - Franz, Bill David, author; Gilley, Jerry, advisor; Smith, Ken, committee member; Lehmann, Jean P., committee member; Good, Glenn, committee member; Gloeckner, Gene, committee member (Colorado State University. Libraries, 2004)
The direct and indirect costs of turnover continue to rise and negatively impact restaurant organizations in many ways. The purpose of this study was to investigate "Generation X" and "Generation Y" restaurant employee perceptions regarding manager/employee relationships on turnover intent and manager relationship satisfaction. Video vignettes of manager/employee communication exchanges addressing poor performance were used as a stimulus and condition of this quantitative study to investigate the cognitive phenomenon of voluntary turnover intent. Generational perceptions were measured using an instrument designed to quantify the effects of the stimulus on turnover intent and manager relationship satisfaction. Initial results indicated no significant interaction effects existed between the generational categories regarding their perceptions of the manager/employee relationship and their link to either turnover intent or manager relationship satisfaction. The study did reveal statistically significant main effects regarding various types of manager/employee relationships, on both turnover intent and manager relationship satisfaction within each generational category. Although not supported by statistical significance, when participants with job tenure of one year or less were isolated, trends in mean scores, standard deviations and accompanying effect sizes reflected an arbitrating influence between the generations and the type of manager/employee relationship on turnover intent and manager relationship satisfaction. Therefore, when faced with a reason to leave, positive relationships play a stronger role for "Generation Y" in decisions to remain with their employers than they do for "Generation X." Similarly, this was indicated for manager relationship satisfaction. Lastly, the study indicated empirical evidence that precursors which impact job tenure are not static and can change with time for members of the restaurant industry's workforce. This study supports the notion that the quality of the manager/employee relationship can affect voluntary turnover intent as well as the level of satisfaction employees perceive concerning the relationships with their managers. It also indicates that within the first year of employment the "Generation Y" workforce places a stronger emphasis on these relationships than does "Generation X."